Konsepsi Imam Syafi’i Tentang Ittihadul Majlis Dalam Akad Nikah - Multazim AA (MAHAKIM Journal of Islamic Family Law, 2020)
Marriage is a basic principle for society to continuoing social life or household life, legal descendants and the destruction of man and women desires. A new couple marriage meets and hope their marriage will be harmonious. One of the pillars of marriage is shighat (Ijab and qabul), which must be Ittihadul Majlis (united in seats or majlis) on Syafi’I School. The Ulama are relatively different in providing concepts /opinions about this matter. Therefore, there needs to be a positive answer, what is the concept / opinion of Imam Syafi’I. Regarding the legal status of Ittihadul Majlis in the akad marriage, considering that the implementation of this in the community is still relatively large on a Shafi’i Madzhab.